Occupational Licensing and the Gender Wage Gap - Maria Koumenta; Mario Pagliero; Davud Rostam-Afschar (Global Labor Organization (GLO), 2020)
We use a unique survey of the EU labor force to investigate the relationship between occupational licensing and the gender wage gap. We find that the gender wage gap is canceled for licensed self-employed workers. However, this closure of the gender wage gap is not mirrored by significant changes in the gender gap in hours worked. Our results are robust using decomposition methods, quantile regressions, different datasets, and selection correction.
Keywords: J16; J31; J44; J71; 330; Licensing; Gender gap; Wages; Female Labour Supply; Quantile regression; Selection